Copyleft, -right and the case law on APIs on both sides of the Atlantic (Journal of Open Law, Technology & Society, 2013)
Like any relatively young areas of law, copyright on software is surrounded by some legal uncertainty. Even moreso in the context of copyleft open source licenses, since these licenses in some respects aim for goals that are the opposite of 'regular' software copyright law. This article provides an analysis of the inheritance effect of the GPL-family of copyleft software licenses (the GPL, LGPL and the AGPL) from a mostly copyright perspective as well as an analysis of the extent to which the SAS/WPL case affects this family of copyleft software licenses. In this article the extent to which the GPL and AGPL inheritance clauses have a wider effect than those of the LGPL is questioned, while both the SAS/WPL jurisprudence and the US Google case seem to affirm the LGPL's “dynamic linking” criterium.